The Changing Physical and Social Environment of Newsgathering: A Case Study of Foreign Correspondents Using Chat Apps During Unrest. (March 2017) - Belair-Gagnon, Valerie; Agur, Colin; Frisch, Nicholas
Mobile chat apps have shaped multiple forms of communication in everyday life, including education, family, business, and health communication. In journalism, chat apps have taken on a heightened significance in reporting political unrest, particularly in terms of audience/reporter distinctions, sourcing of information, and community formation. Mobile phones are now essential components in reporters' everyday communication, and particularly during political unrest. In East Asia, the latest trends point toward private networking apps, such as WeChat and WhatsApp, as the most important digital tools for journalists to interact with sources and audiences in news production. These apps provide a set of private (and, increasingly, encrypted) alternatives to open, public-facing social media platforms. This article is the first to examine foreign correspondents' usage of chat apps for newsgathering during political unrest in China and Hong Kong since the 2014 "Umbrella Movement, " a time when the use of chat apps in newsgathering became widespread. This article identifies and critically examines the salient features of these apps. It then discusses the ways these journalistic interactions on chat apps perpetuate, disrupt, and affect "social" newsgathering. This article argues that chat apps do not represent one interactive space; rather they are hybrid interactions of news production embedded in social practices rather than pre-existing physical/digital spaces. This research is significant as the emergence of chat apps as tools in foreign correspondents' reporting has implications for journalistic practices in information gathering, storage, security, and interpretation and for the informational cultures of journalism.